2009
DOI: 10.1017/s0263574709005621
|View full text |Cite
|
Sign up to set email alerts
|

Design, implementation, and performance evaluation of a 4-DOF parallel robot

Abstract: This paper deals with the design, implementation, and performance evaluation of a new type of 4-DOF parallel mechanism providing three translations and one rotation for high-speed handling and machining. This parallel mechanism is named H4. A necessary condition and system configuration of the H4 are also described. Hardware and kinematics of the H4 is addressed and the manipulability ellipsoid which is one of the widely used methods to examine the design of parallel mechanisms is addressed. The performance ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…The inverse solution of the algebraic method [3,4] is based on the triangular transformation relationship between the parameters of the final transformation matrix, we can easily get one or several joint angle by substitute the corresponding values of corresponding parameters of the end effector matrix. The geometric method [5,6] is proposed by C.S.G.Lee in 1982,it is used to solve inverse kinematic by the triangle relation between the joint variable and links according to the structure.…”
Section: Inverse Kinematicsmentioning
confidence: 99%
“…The inverse solution of the algebraic method [3,4] is based on the triangular transformation relationship between the parameters of the final transformation matrix, we can easily get one or several joint angle by substitute the corresponding values of corresponding parameters of the end effector matrix. The geometric method [5,6] is proposed by C.S.G.Lee in 1982,it is used to solve inverse kinematic by the triangle relation between the joint variable and links according to the structure.…”
Section: Inverse Kinematicsmentioning
confidence: 99%
“…Conventionally, the global kinematic performance indices can be represented by the mean value [4] and standard deviation [5,6] of algebraic characteristics of the Jacobian throughout the entire workspace, for example, its condition number, minimum singular value and determinate. Some of these have been widely accepted and extended into various modified versions to deal with the kinematic dimensional synthesis problem of 2-4 DOF Delta-like parallel robots [7][8][9][10][11][12][13]. However, merely optimizing the kinematic performance indices is not adequate because the inertial and centrifugal/Coriolis effects must be taken into account when such a robot runs at very high-speed and high-acceleration.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that such manipulators can be used to avoid singularities inside the workspace of non-redundant manipulators. Choi et al (2010) developed a new 4-DOF parallel mechanism with three translational and one rotational movements and found this mechanism to be ideal for high-speed machining. Gao et al (2010) proposed a novel 3DOF parallel manipulator and they increased the stiffness of their system, using an optimization technique.…”
Section: Introductionmentioning
confidence: 99%